196k views
0 votes
Someone PLS HELP <3

Solve the system of equations using the substitution method.

{y=−3x+7
x=−2y−16



Enter your answers in the boxes.

x =

y =

User Billschen
by
6.6k points

1 Answer

0 votes
y = -3x + 7
x = -2y - 16

Substitute the top expression for y in the bottom equation:

x = -2y - 16
x = -2(-3x + 7) - 16
x = 6x - 14 - 16
x = 6x - 30
-5x = -30
x = 6

Substitute back into one of the original equations:

y = -3x + 7
y = -3(6) + 7
y = -18 + 7
y = -11

Lastly, substitute back into both original equations:

y = -3x + 7 => -11 = -3(6) + 7 => -11 = -18 + 7 <--True
x = -2y - 16 => 6 = -2(-11) - 16 => 6 = 22 - 16 <--True

Answer:
x = 6
y = -11
User Kyree
by
6.1k points